Tanshinone IIA Ameliorates Nonalcoholic Steatohepatitis in Mice by Modulating Neutrophil Extracellular Traps and Hepatocyte Apoptosis. (1st September 2022) - Xu, Lianjie; Liu, Xiao; Jia, Tao; Sun, Yanhong; Du, Yan; Wei, Shanshan; Wang, Wei; Zhang, Yurong; Chen, Wenhui; Zhang, Shan
Abstract : Salvia miltiorrhiza Bunge, a traditional Chinese medicine, is widely used in the treatment of a variety of diseases and syndromes. Tanshinone IIA (TIIA), a phenanthrenequinone-class derivative extracted from S. miltiorrhiza, is one of its main active components and has anti-inflammatory effects on various tissues and cells. This study aimed to investigate the beneficial effects of TIIA on nonalcoholic steatohepatitis (NASH) induced in mice using a methionine choline deficiency (MCD) diet and the underlying mechanism of these. Our results reveal that TIIA remarkably ameliorated hepatic steatosis and inflammation and decreased the serum levels of liver dysfunction markers while increasing the levels of serum total cholesterol and triglycerides in MCD-fed mice. TIIA significantly reduced mRNA levels of the inflammatory factors TNF- α, IL-6, and TGF- β . Similarly, TIIA inhibited caspase-3 and Bax-mediated apoptosis in MCD-fed mice. Together, our data indicate that TIIA inhibits the formation of MPO and CitH3 in neutrophil extracellular traps and inhibits apoptosis mediated by caspase-3 and Bax in hepatocytes, thereby mitigating inflammatory progression in an MCD diet-induced NASH mouse model.